Strategic Communication and Sustainability: A Qualitative Study of Ngo Operated Malaysian Aged Care Centers - Nadzmy, Nurul Fadzlyn Enche; Hassan, Nik Hasfizul; Mohamad, Shafi; Sing, Ramila Devi Ram (Indian Journal of Information Sources and Services, 2025)
A significant increase in Malaysia’s elderly population is causing a surge in demand for aged care centers run by nongovernmental organizations (NGOs). As a result, effective communication is essential for NGOs in driving sustainability, particularly by strengthening transparency, building trust, and engaging stakeholders. This study investigates the link between communication strategies and sustainability of Malaysian aged care centers of NGOs. To achieve better understanding, data collection was conducted using a qualitative research strategy with semi-structured interviews. The study’s sample consisted of ten (10) aged care centers located in Kuala Lumpur and Selangor, Malaysia. The findings indicated that NGOs have incorporated effective communication tactics into their organizations, resulting in a greater impact on their sustainability. According to the findings, organizations that execute communication strategies that are targeted, transparent, and participative are in a better position to gain the trust of donors, attract volunteers, and establish long-term partnerships. A recommendation plan has been developed based on the findings. This study proposes a system that incorporates effective communication strategies in aged care centers run by Malaysian NGOs. Therefore, identifying communication methods that are relevant to Malaysia will contribute to the current body of knowledge, and these insights are critical for NGO boards and legislators concerned with sustainability over the long term and public accountability.